Práticas e saberes dos enfermeiros da atenção básica acerca da colpocitologia oncótica e inspeção visual - Franco, Rosana Gomes de Freitas Menezes (2013)
The high morbidity and mortality rates for Cervical Cancer (CC) in Brazil may be due to the low population coverage of Oncotic Colpocytology (OC), as well as insufficient and/or inadequate therapeutic and diagnostic conducts. This study aimed to evaluate the practices and knowledge of primary care nurses about CC and visual inspection. This was a cross-sectional descriptive correlational study in a higher education institution in Juazeiro do Norte-CE. The sample was not probabilistic obtained by convenience, totaling 144 nurses. A questionnaire with information about the nurses’ knowledge about the Visual Inspection with Acetic Acid was applied, the Schiller test, recognition and ability to technically describe structures that are observed in the daily practice of nursing gynecologic consultations and the professional’s efficacy and safety in indicating the diagnosis depth when faced with a change suggesting cervical HPV infection, regardless the result of the CC. Exploratory data analysis took advantage of absolute and relative frequencies, means and standard deviations, and the analysis of categorical variables. It was found that most respondents were between 26 and 30 years (N = 78; 54.2%), with one year or less (N = 48; 33.3%) of professional experience, and who exercised their activities in the FHP (N = 100; 69.4%), especially in Juazeiro do Norte (N = 49; 34%). It was also found that 96.5% believed that there were still many unknown or new information on workup of CC and 97.2% recognized the need to receive updates, 68.1% said that participation in training does not interfere in other professional activities. It was noticed that the previous experience of nurses presented in the visualization of the clinical finding ranged from 14.6% to 48.6%. In the evaluation of the nurses’ practices and knowledge about the Schiller Test, a higher percentage of the nurses’ accuracy was only 9.7% with respect to the conservation of this solution. Concerning the description of the structures identified in the clinical images, the structure with the highest percentage of correctness (5.5%) among nurses was the identification of the cervical canal and the squamocolumnar junction. It was found that the baseline knowledge of the morphology of the cervix and the ability to recognize abnormal structures was insufficient for most of the nurses to perform safely the IV and the Schiller Test. Given this result it is important to conduct training with these professionals, a fact that is corroborated by their interest and motivation in relation to these strategies.